Enhancing the selectivity for light olefins through catalytic cracking of n-hexane by phosphorus doping on lanthanum-modified ZSM-5 - Muhammad Faryad Ali; Mu He; Muhammad Rizwan; Yueqin Song; Xiaolong Zhou; Muhammad Asif Nawaz; Hui Sun; Mengke Zhou; Peng Jiang (Frontiers in Chemistry, 2024)
Naphtha, as the primary raw material in the production of light olefins, could well accommodate their increasing demand through the energy-efficient process of catalytic cracking with ZSM-5. In the current work, different amounts of lanthanum and phosphorous were loaded on ZSM-5 using the wet impregnation method to tune the acidic properties of ZSM-5 for selective catalytic cracking of n-hexane to produce light olefins. Various characterization techniques such as X-ray diffraction (XRD), Al nuclear magnetic resonance (NMR), temperature-programmed desorption of NH3 (NH3-TPD), Py-Fourier transform infra-red (Py-FTIR), inductively coupled plasma optical emission spectroscopy (ICP-OES), N2 adsorption–desorption, X-ray photoelectron spectra (XPS), and scanning electron microscopy were adopted to investigate the modified zeolites. It was found that adding La to ZSM-5 (0.25 wt% to 1 wt%) improved the catalytic life and increased the n-hexane conversion (to 99.7%), while the further addition had a negative impact, reducing the conversion rate and deviating the product selectivity towards a substantial, undesired benzene, toluene, and xylene (BTX) fraction (33%). On the other hand, a 64% selectivity for light olefins was achieved on phosphorous-doped ZSM-5 (at a loading amount of 1 wt%) while reducing the BTX fraction (2.3%) and converting 69% of the n-hexane. A dual metal-modified ZSM-5 with optimal loading amount, 1P0.25LaZ5 (phosphorus 1 wt% and La 0.25 wt%), helped boost the light olefin selectivity to 62% in the tuned Lewis acid sites at an n-hexane conversion of about 77% while decreasing the undesired BTX selectivity to 3% by reducing the number of Brønsted sites. Thus, the current study reveals that tuning the acidic sites of ZMS-5 by dual metal augmentation with P.La is an effective way of controlling the amount of undesirable BTX produced at a stable n-hexane conversion rate and substantial olefin selectivity.